From Submission to Contract: An Evaluation on the Management Process of Research Proposals in Tehran University of Medical Sciences - Koroush Holakouie-Naieni; Shahrzad Nematollahi; Ahmad Reza Shamshiri; Hossein Ansari; Majid Mirmohammadkhani (Tehran University of Medical Sciences, 2021)
None